Small isn't beautiful. Construction worker deaths 2007/8: employer size and circumstance. A UCATT report (London, 2009)
"This report provides detailed information on the deaths of construction workers reported to the Health and Safety Executive in the year between 1 April 2007 and 31 March 2008, and it considers whether those in the construction sector working for smaller employers are at greater risk of suffering fatal injury than those working for larger companies. The report was been produced by the Centre for Corporate Accountability for the trade union UCATT."